Predictors of midwives’ intention to provide planned home birth services to low-risk women: a theory of planned behaviour approach - Muhammed, Auwalu; Lee, Khuan; Shariff Ghazali, Sazlina; Md Said, Salmiah; Md Said, Salmiah; Hassan, Mairo (Elsevier Ltd, 2019)
Objective: Planned home birth may increase women’s access to skilled midwives in all settings. Using theory to understand and predict midwives’ intention regarding planned home birth services is rare. Therefore, using the theory of planned behaviour, we determined the factors associated with midwives’ intention to provide planned home birth services to low-risk women. Design: This cross-sectional study adopted a quantitative approach and a survey. Stratified random sam- pling was used to recruit 226 midwives in Sokoto, Nigeria. Data—including descriptive statistic and mul- tiple linear regression analyses—were analysed using SPSS 23 and significant was set at 0.05. Setting: Ten public health facilities in Sokoto, northwestern Nigeria. Participants: Among all 460 midwives (women aged 20–60 years), working in the maternity wards of health facilities in Sokoto, a sample of 226 midwives was calculated using a power of 0.80 and a 95% confidence interval. Findings: The multiple linear regression analyses confirmed that the major factors associated with mid- wives’ intention to provide planned home birth services were midwives’ attitude towards planned home birth (p < .001) and midwives’ previous experience with planned home birth practice (p = .008). Conclusions and implications: The theory of planned behaviour is a useful framework for identifying fac- tors that affect midwives’ intention to provide planned home birth services. While future research may employ a qualitative approach to explore other factors, planned home birth education campaigns should target information that enhances positive attitude and encourages midwives to provide planned home birth services.